Study on the Performance of a Quasi-Zero-Stiffness Isolator with Time Delay Control (Xibei Gongye Daxue Xuebao, 2018)
A quasi-zero-stiffness vibration isolation consists of a pair of oblique springs and a vertical spring, aiming at widening the vibration isolation region, is studied in this paper. The time delay linear displacement feedback control strategy is introduced to improve the performance of the isolator. The characteristics of dynamical response under harmonically forcing excitation is obtained by using averaging method. The force transmissibility of the control isolator is presented in this paper. The influence of the time delay linear displacement control on the force transmissibility is studied theoretically. The results show that the performance of the vibration isolation with time-delay control is better than the equivalent linear isolator in either low or high frequency region and the performance of controlled system is better than uncontrolled system.